2018
DOI: 10.22219/kinetik.v4i1.687
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acquisition Software for Digital Forensics Purposes

Abstract: Digital Forensics, a term that is increasingly popular with internet needs and increasing cybercrime activity. Cybercrime is a criminal activity with digital media as a tool for committing crimes. The process for uncovering cybercrime is called digital forensics. The initial stage in digital forensics is an acquisition. The acquisition phase is very important because it will affect the level of difficulty and ease in investigating cybercrime. Software acquisition will affect the abandoned artefacts and even ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…A study in [12] compared four tools, namely Windows Memory Reader, Belkasoft"s Live Ram Capturer, ProDiscover, and FTK Imager, to examine their performance in capturing memory including their ease of use. Another study in [13] showed the differences in processing time, memory usage, registry key, and DLL for FTK Imager, Belkasoft RAM Capturer, Memoryze, DumpIt, and Magnet RAM Capturer. Similarly, [14] also examined how the combination of Belkasoft RAM Capturer, FTK Imager, and Winhex can be utilized to obtain data for the Line app in Windows 8.1.…”
Section: Related Workmentioning
confidence: 99%
“…A study in [12] compared four tools, namely Windows Memory Reader, Belkasoft"s Live Ram Capturer, ProDiscover, and FTK Imager, to examine their performance in capturing memory including their ease of use. Another study in [13] showed the differences in processing time, memory usage, registry key, and DLL for FTK Imager, Belkasoft RAM Capturer, Memoryze, DumpIt, and Magnet RAM Capturer. Similarly, [14] also examined how the combination of Belkasoft RAM Capturer, FTK Imager, and Winhex can be utilized to obtain data for the Line app in Windows 8.1.…”
Section: Related Workmentioning
confidence: 99%
“…Setiap tahun selalu meningkat baik dari sisi jumlahnya maupun variasi kejahatannya. Internet dahulu hanya untuk mengirimkan email saja, tetapi sekarang internet telah digunakan diberbagai aktivitas pekerjaan dan kehidupan manusia seperti mengirim gambar, video, data dapat dikirimkan dengan mudah dan cepat [2]. Kejahatan di internet muncul karena adanya komunikasi dan hubungan antara satu komputer dengan komputer yang lain melalui suatu jaringan [3].…”
Section: Gambar 1 Pertumbuhan Pengguna Internet DI Indonesiaunclassified
“…People often use different digital media like PCs, PDAs, laptops, cell phones, and some other digital devices and use them for communication purposes. One of the main sources of communication is the internet, the internet itself can cause several crimes or better known as cybercrimes, which result in damage such as data theft or dangerous system activities [2]. The people who have the responsibility to commit such cybercrimes are required for their capabilities and procedures to prevent or carry out such attacks [3].…”
Section: Introductionmentioning
confidence: 99%